Sustainability of a Residential CFL Distribution Program : Evidence from Ethiopia - Diaw, Issa; Elahi, Raihan; Iimi, Atsushi (World Bank, Washington, DC, 2016)
Energy-efficient products generally offer a win-win proposition, because they pay for themselves. End users can reduce their energy costs, and power utilities can avoid costly investments in extra generation capacity. Moreover, energy efficiency can contribute to mitigating global warming. This paper casts light on the sustainability of the residential use of compact fluorescent lamps after the free compact fluorescent lamp distribution program in Ethiopia. It is found that the direct program effect has been sustained for at least four years after the program. The effect of the distributed compact fluorescent lamps may taper off, if some of the program beneficiaries reinstall relatively cheap incandescent bulbs when the compact fluorescent lamps are burned out. However, many households replaced burned out compact fluorescent lamps with new compact fluorescent lamps. This effect is found to be statistically significant, particularly among relatively low-income households, whose demand is more price-elastic. All the indications are that program participants were generally convinced that compact fluorescent lamp bulbs are more cost-effective in the long run and the program effect is sustained over time.